The effects of face tape and face tape residue on ball flight characteristics - Wells, J. E. T.; Dye, P. T. (International Journal of Golf Science, 2025)
Face tape is commonly used by custom fitters, however, when removed, it can leave adhesive residue on the clubface. This study assessed the effects of three clubface conditions on ball flight. Twenty golfers hit shots under three conditions: 1) clean, 2) face tape, and 3) adhesive residue using both a 5-iron and 7-iron. Data were collected using a TrackMan 4 launch monitor at a driving range. Statistical analysis was conducted using MANOVA, with post hoc assessment via least significant differences. No differences were observed for the 5-iron data. The 7-iron produced a higher launch angle and significantly greater spin than the 5-iron across all conditions. Additionally, the 7-iron generated a significantly higher launch angle, lower spin, and greater distance under the face tape condition compared to the clean and residue clubs. It is recommended that researchers and practitioners use clean clubs when collecting golf data to ensure consistency and accuracy.